If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 = -25 + -2x Reorder the terms: 1 + 5x = -25 + -2x Solving 1 + 5x = -25 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 1 + 5x + 2x = -25 + -2x + 2x Combine like terms: 5x + 2x = 7x 1 + 7x = -25 + -2x + 2x Combine like terms: -2x + 2x = 0 1 + 7x = -25 + 0 1 + 7x = -25 Add '-1' to each side of the equation. 1 + -1 + 7x = -25 + -1 Combine like terms: 1 + -1 = 0 0 + 7x = -25 + -1 7x = -25 + -1 Combine like terms: -25 + -1 = -26 7x = -26 Divide each side by '7'. x = -3.714285714 Simplifying x = -3.714285714
| 80x^4+72x^3-47x^2-15x=0 | | 3t-15=2+10 | | (2+z)(4z-1)=0 | | 3cosx*sinx=1 | | 4x-18=3x+5 | | 6(t-2)+4t=5(2t+4)-9 | | (s)(-3st)(-1/3) | | y+115+65= | | 3x+6=6x+20 | | logbase(2x+6)144=2 | | -2(3x+2)=-48 | | Sin^2x-2cosx-2=0 | | 5(6x-4)=34x | | 10-2w=6 | | 2u+2=5p-10 | | 1+-2g=5 | | 4/15-3/15 | | 13a-1=90 | | -(6y+3)-(-5-4)=-7 | | P=4c-20+2c | | 73=4p+7 | | 2=4-2y | | F(x)=x*2+6x+15 | | -3(5s-2)-6=-3(9s+2)-5 | | -9=3k+-3 | | 2y^2-12y+8=0 | | 50=65+10t-5t^2 | | 3x^2+78=0 | | .65x+.05(14-x)=.10(-17) | | 5=a/-11 | | .18(24)+.03x=.09(18+x) | | 1/5y+11=3-3/5y |